Enhanced light extraction efficiency of UV LEDs by encapsulation with UV-transparent silicone resin. (1st June 2022) - Wu, Shaojun; Guttmann, Martin; Lobo-Ploch, Neysha; Gindele, Frank; Susilo, Norman; Knauer, Arne; Kolbe, Tim; Raß, Jens; Hagedorn, Sylvia; Cho, Hyun Kyong; Hilbrich, Katrin; Feneberg, Martin; et al.
Abstract: Increase of light extraction efficiency (LEE) and total output power of UV light emitting diodes (LEDs) emitting at 265 and 310 nm, respectively, after encapsulation with a UV-transparent silicone are studied. Raytracing simulations suggest that a properly placed hemispherical encapsulation with a refractive index in the range from 1.4 to 1.8 enhances the LEE from 8% to up to 16% for flip-chip mounted UV LEDs with non-reflective metal contacts. The simulations also show that the absorption coefficient of the encapsulant determines the maximum LEE and optimum dome diameter and that it should be below 3 cm −1 . The silicone encapsulant exhibits a refractive index of 1.47 (1.45) and an absorption coefficient of 1.3 cm −1 (0.47 cm −1 ) at 265 nm (310 nm). AlGaN/sapphire-based UVC and UVB LED chips were flip-chip mounted on planar AlN ceramic packages and encapsulated with a 1.5 mm-radius hemispherical silicone dome. The total output power at an operation current of 350 mA increased from 27 to 46 mW for 265 nm LEDs and from 45 to 78 mW for 310 nm LEDs. This corresponds to an enhancement of about 70%, which agrees with the simulations. Moreover, far-field measurements of encapsulated LEDs showed a narrowing of the emission cone.